2019
DOI: 10.1021/jacs.9b07626
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Electron Dynamics in Atomically Precise Nanoclusters with Eight Superatomic Electrons

Abstract: The [Au25(SR)18]− and [Au13(dppe)5Cl2]3+ [dppe = 1,2-bis­(diphenylphosphino)­ethane] nanoclusters both possess a 13-atom icosahedral core with 8 delocalized superatomic electrons (8e), but their emission properties and time-resolved electron dynamics differ significantly. In this work, experimental photoluminescence and photoluminescence decay measurements are combined with time-dependent density functional theory calculations of radiative and nonradiative decay properties and lifetimes to elucidate the simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 111 publications
(158 reference statements)
5
74
0
1
Order By: Relevance
“…23 Furthermore, density functional theory (DFT) calculations indicated that a metallic (Au 13 ) 5+ core can be viewed as a superatom with a closed electron conguration of (1s) 2 (1p) 6 . 43 Despite extensive studies, the effects of halide ligands on the PL or electronic structures of Au 13 clusters have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, density functional theory (DFT) calculations indicated that a metallic (Au 13 ) 5+ core can be viewed as a superatom with a closed electron conguration of (1s) 2 (1p) 6 . 43 Despite extensive studies, the effects of halide ligands on the PL or electronic structures of Au 13 clusters have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…18 Toward this goal, signicant efforts have been made in recent years. [25][26][27][28][29][30][31][32][33][34][35][36][37] Wu et al identied that the presence of electron-rich atoms (e.g., oxygen and nitrogen) or functional groups (e.g., the carboxyl or amine group) in the thiolate ligands could enhance the PL of Au 25 (SR) 18 nanoclusters via ligand to metal core charge transfer. 25 Xie et al reported an aggregation induced emission (AIE) mechanism in gold nanoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] With the valuable structural information, it has become possible to precisely correlate the PL properties of gold nanoclusters with the atomic structure. 33 For thiolate-protected Au n (SR) m nanoclusters, both the inner gold kernel (hereaer referred to as core) and surface Au x (SR) x+1 motifs (hereaer referred to as shell) are considered as important contributors to their PL properties. 28,56 For the well-studied icosahedral Au 25 (SR) 18 nanocluster, the core-to-shell relaxation was observed in ultrafast electron dynamics and the PL mechanism was interpreted, [57][58][59][60][61] including the theoretical insights.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Among these properties, photoluminescence (PL) is one of the most fascinating, both theoretically and experimentally, due to the plethora of promising PL-based applications. [48][49][50][51][52][53][54][55][56][57][58][59][60] Particular attention has been focused on understanding mechanisms of the PL of nanoclusters and then controlling the synthesis of more highly emissive nanoclusters. [48][49][50][51][52][53][54][55][56][57][58][59][60] Aggregation-induced emission (AIE), a photophysical phenomenon wherein nanomaterials that are nonluminescent or weakly luminescent become highly luminescent upon aggregation, has been extensively exploited for preparing strongly emissive cluster-based nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51][52][53][54][55][56][57][58][59][60] Particular attention has been focused on understanding mechanisms of the PL of nanoclusters and then controlling the synthesis of more highly emissive nanoclusters. [48][49][50][51][52][53][54][55][56][57][58][59][60] Aggregation-induced emission (AIE), a photophysical phenomenon wherein nanomaterials that are nonluminescent or weakly luminescent become highly luminescent upon aggregation, has been extensively exploited for preparing strongly emissive cluster-based nanomaterials. [61][62][63][64][65][66][67][68][69] As for the mechanism of the nanocluster AIE, it has been accepted that orderly aggregation would reduce the energy loss of photoexcited clusters through nonradiative transitions, and the energy released through the radiative transition (i.e., PL) would increase accordingly.…”
Section: Introductionmentioning
confidence: 99%